HIV/AIDS Dynamics with Three Control Strategies: The Role of Incidence Function. (13th August 2012) - Kateme, Emmanuelina L.; Tchuenche, Jean M.; Hove-Musekwa, Senelani D.
Abstract : The type of incidence function used in epidemiological models is generally a matter of choice and convenience. Basic deterministic HIV/AIDS models with standard and saturated incidences are developed and extended to include three control measures, namely, public health educational campaigns, condom use, and treatment. The potential impact of these incidence functions on long-term projection of the disease dynamics is theoretically assessed, both qualitatively and quantitatively. Conditions for the stability of the model steady states are provided. The model with saturated incidence yields a higher number of secondary infections compared to the same outcome in the standard incidence formulation.